2022
DOI: 10.1016/j.mrrev.2022.108411
|View full text |Cite
|
Sign up to set email alerts
|

The potential role of COVID-19 in the induction of DNA damage

Abstract: The coronavirus disease-2019 (COVID-19) caused by the severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) is challenging global health and economic systems. In some individuals, COVID-19 can cause a wide array of symptoms, affecting several organs, such as the lungs, heart, bowels, kidneys and brain, causing multiorgan failure, sepsis and death. These effects are related in part to direct viral infection of these organs, immunological deregulation, a hypercoagulatory state and the potential for develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
16
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 91 publications
2
16
1
1
Order By: Relevance
“…A recent review suggested that SARS-CoV2 induces S-phase cell cycle arrest by promoting replication fork stress, possibly through its virus protein nsp13 which is known to interfere with DNA polymerase δ (POLD). 49 We do not know how POLD functions in Covid-19 patients based, but we do however observe an increase of POLD1 protein levels in PBMC and upregulation of POLD3 in regulatory T cells. However, cell cycle regulators do also have important immunomodulatory roles in, for example, interferon signaling and T cell activation.…”
Section: Discussioncontrasting
confidence: 57%
“…A recent review suggested that SARS-CoV2 induces S-phase cell cycle arrest by promoting replication fork stress, possibly through its virus protein nsp13 which is known to interfere with DNA polymerase δ (POLD). 49 We do not know how POLD functions in Covid-19 patients based, but we do however observe an increase of POLD1 protein levels in PBMC and upregulation of POLD3 in regulatory T cells. However, cell cycle regulators do also have important immunomodulatory roles in, for example, interferon signaling and T cell activation.…”
Section: Discussioncontrasting
confidence: 57%
“…DNA damage response and repair mechanisms have been involved in the pathogenesis of chronic conditions such as diabetes and cardiovascular disease [ 66 ]. However, the role of SARS‐CoV‐2 in inducing genome instability has not been fully ascertained.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that in ammation and oxidative stress in viral infections have genotoxic effects [35]. Chronic in ammation increases the formation of reactive oxygen species [36].…”
Section: Discussionmentioning
confidence: 99%